2021
DOI: 10.3390/s21062070
|View full text |Cite
|
Sign up to set email alerts
|

Design and Modification of a High-Resolution Optical Interferometer Accelerometer

Abstract: The Micro-Opto-Electro-Mechanical Systems (MOEMS) accelerometer is a new type of accelerometer that combines the merits of optical measurement and Micro-Electro-Mechanical Systems (MEMS) to enable high precision, small volume, and anti-electromagnetism disturbance measurement of acceleration, which makes it a promising candidate for inertial navigation and seismic monitoring. This paper proposes a modified micro-grating-based accelerometer and introduces a new design method to characterize the grating interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The sensitivity of the accelerometer has reached 619 V/g. A similar study was done by Lu et al with good results [66][67][68][69][70], and the specific parameters are shown in Table 3.…”
Section: Optical Intensity Modulationsupporting
confidence: 55%
“…The sensitivity of the accelerometer has reached 619 V/g. A similar study was done by Lu et al with good results [66][67][68][69][70], and the specific parameters are shown in Table 3.…”
Section: Optical Intensity Modulationsupporting
confidence: 55%
“…According to Equations ( 6) and ( 7), the Brownian noise of the accelerometer can be reduced by increasing the mass of the moving system, reducing the resonance frequency and increasing the Q-factor [42]. A massive mechanical system is difficult to fabricate, while the reduction in the stiffness is less consuming.…”
Section: Coupling Lengthmentioning
confidence: 99%
“…[12] Yuan Yao et al integrated VCSELs and photodiode (PD) arrays on a single chip, which further contributed to the miniaturization and stability of the sensor structure while improving the sensor's accuracy. [13] Eitel et al proposed a VCSEL chip with an integrated microlens array, it is used for laser shaping, which effectively improves the interferometric sensitivity of the accelerometer (Figure 4c). [14] To Figure 3.…”
Section: Diffraction Grating Interference Accelerometermentioning
confidence: 99%